Prognostic value of a combination of innovative factors (gut microbiota, sarcopenia, obesity, metabolic syndrome) to predict surgical/oncologic outcomes following surgery for sporadic colorectal cancer: a prospective cohort study protocol (METABIOTE). Issue 1 (7th January 2020) - Veziant, Julie; Poirot, Karine; Chevarin, Caroline; Cassagnes, Lucie; Sauvanet, Pierre; Chassaing, Benoit; Robin, Frederic; Godfraind, Catherine; Barnich, Nicolas; Pezet, Denis; Pereira, Bruno; Gagniere, Johan; et al.
Abstract : Introduction: Colorectal cancer (CRC) is still associated with poor prognosis, especially in patients with advanced disease. Development of new prognostic tools replacing or supplementing those routinely used is definitely needed, with the aim to optimise and personalise treatment strategies. Gut microbiota composition and body composition profile (obesity, sarcopenia and metabolic syndrome) have recently been reported separately as new relevant prognostic factors for postoperative surgical and oncologic outcomes following CRC surgery. However interactions that exist between these factors have been poorly studied. The purpose of this translational prospective cohort study (METABIOTE) is to investigate potential interactions between gut microbiota, body composition profile and postoperative outcomes and recurrence in patients undergoing surgery for non-metastatic sporadic CRC. Methods and analysis: This single-centre project aims to prospectively enrol 300 consecutive patients undergoing surgery for non-metastatic sporadic CRC at the University Hospital of Clermont-Ferrand, France for the identification of specific microbial signatures (from tumour, colonic mucosa and stools samples) associated with particular metabolic profiles that could impact postoperative morbidity and oncologic outcomes, using microbiological, molecular and imaging approaches. The primary outcome is the 5-year overall survival (OS). Other outcomes are 5-year CRC-related OS, 5-year disease-free survival, 30-day postoperative morbidity, 90-day postoperative mortality and length of hospital stay. Ethics and dissemination: This study protocol was reviewed and approved by an independent French regional review board (n°2018-A00352-53, 'Comité de Protection des Personnes Ile de France VII' on 4 July 2018, declared to the competent French authority ('Agence Nationale de Sécurité du Médicament et des produits de santé', France), and registered on the Clinical Trials web-based platform (NCT 03843905). Oral and written informed consent will be obtained from each included patient. Study results will be reported to the scientific community at conferences and in peer-reviewed scientific journals. Trial registration number: NCT03843905 . .